2013
DOI: 10.1038/mp.2013.146
|View full text |Cite
|
Sign up to set email alerts
|

Common genetic variants on 1p13.2 associate with risk of autism

Abstract: Autism is a highly heritable neurodevelopmental disorder, and known genetic variants, mostly rare, account only for a small proportion of cases. Here we report a genome-wide association study on autism using two Chinese cohorts as gene discovery (n=2150) and three data sets of European ancestry populations for replication analysis of top association signals. Meta-analysis identified three single-nucleotide polymorphisms, rs936938 (P=4.49 × 10(-8)), non-synonymous rs6537835 (P=3.26 × 10(-8)) and rs1877455 (P=8.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
77
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(80 citation statements)
references
References 37 publications
1
77
0
2
Order By: Relevance
“…Unr has been implicated in the control of cell death (Dormoy-Raclet et al, 2007), cell differention (Elatmani et al, 2011) and cell migration (Kobayashi et al, 2013). In humans, recent studies identified important roles for Unr in the promotion of melanoma cell invasion and metastasis (Wurth et al, 2016), as well as in disorders, such as autism or Diamond-Blackfan anemia (Sanders et al, 2012;Xia et al, 2014;Horos and von Lindern, 2012). Unr has also been characterized as being a critical regulator of embryonic development.…”
Section: Introductionmentioning
confidence: 99%
“…Unr has been implicated in the control of cell death (Dormoy-Raclet et al, 2007), cell differention (Elatmani et al, 2011) and cell migration (Kobayashi et al, 2013). In humans, recent studies identified important roles for Unr in the promotion of melanoma cell invasion and metastasis (Wurth et al, 2016), as well as in disorders, such as autism or Diamond-Blackfan anemia (Sanders et al, 2012;Xia et al, 2014;Horos and von Lindern, 2012). Unr has also been characterized as being a critical regulator of embryonic development.…”
Section: Introductionmentioning
confidence: 99%
“…Some of these rare single point genetic mutations, or even common genetic variants, have also been associated inconsistently with autism. 4,9,15,16 At present, the diagnosis of autism relies mainly on some observational tools that may involve a great variability. Few biomarkers are established for autism.…”
Section: Introductionmentioning
confidence: 99%
“…Xia et al used two Chinese cohorts for gene discovery (n=2150) and three data sets of European ancestry populations for replication analysis of top association signals. Meta-analysis identified three single-nucleotide polymorphisms and related haplotypes; all were mapped to a previously reported linkage region (1p13.2) with autism [26]. Kovac et al identified two single nucleotide polymorphisms (SNPs).…”
Section: Common Genetic Variants In Asdmentioning
confidence: 99%
“…Manual examination of this list identified ANK3 as the most likely candidate gene [25]. Xia et al suggested TRIM33 and NRAS-CSDE1 as candidate genes for autism, and may provide a novel insight into the etiology of autism [26].…”
Section: Candidate Genes In Asdmentioning
confidence: 99%